2022
DOI: 10.3389/fphar.2022.937759
|View full text |Cite
|
Sign up to set email alerts
|

Status and Trends of the Association Between Diabetic Nephropathy and Diabetic Retinopathy From 2000 to 2021: Bibliometric and Visual Analysis

Abstract: Background: Diabetic nephropathy (DN) and diabetic retinopathy (DR) are microvascular complications of diabetes that share a similar pathogenesis and clinical relevance. The study aimed to visually analyze the research status and development trend of the relationship between DN and DR by means of bibliometrics and knowledge mapping.Methods: Publications were collected from the Science Citation Index-Expanded of the Web of Science Core Collection between 2000 and 2021. CiteSpace, Alluvial Generator, and Microso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, compared with the non-DR-worsening group, the patients in the DR-worsening group had worse kidney function and a greater frequency of diabetic nephropathy. Current studies have confirmed that diabetic nephropathy is closely related to DR, especially PDR or severe NPDR in diabetic patients [ 32 34 ]. Similarly, diabetic nephropathy was found to be an independent risk factor of DR-worsening after PRP.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, compared with the non-DR-worsening group, the patients in the DR-worsening group had worse kidney function and a greater frequency of diabetic nephropathy. Current studies have confirmed that diabetic nephropathy is closely related to DR, especially PDR or severe NPDR in diabetic patients [ 32 34 ]. Similarly, diabetic nephropathy was found to be an independent risk factor of DR-worsening after PRP.…”
Section: Discussionmentioning
confidence: 93%
“…Adopting coping strategies for coping with DR entails educating oneself about the condition, scheduling routine comprehensive eye exams, managing blood sugar levels, controlling blood pressure and cholesterol, adhering to medication regimens, implementing lifestyle modifications, utilizing visual aids, seeking emotional support, participating in support groups, and accessing rehabilitation services as needed [ 81 ]. Self-management encompasses routine blood pressure monitoring, discussing pregnancy plans with healthcare providers for potential treatment adjustments, adhering to a nutritious diet, engaging in regular physical activity, abstaining from smoking, and adhering to prescribed medication regimens [ 82 ]. These self-care practices profoundly influence treatment outcomes and the progression of DR.…”
Section: Reviewmentioning
confidence: 99%
“…Although some literature reviews and meta-analyses can present summary findings, these means usually fail to achieve the capture of changing trends in publications, the evaluation of research contributions, and the prediction of research hotspots. Bibliometric analysis is a method that employs statistical and mathematical techniques to analyze scientific literature both qualitatively and quantitatively, which is used to detect research status and hotspots in a specific area ( Lin et al, 2022 ). Moreover, bibliometrics can use relevant parameters to present contributions from different countries, institutions, and authors to help with subsequent experimental strategies and funding decisions ( Deng et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%